The CARMENES search for exoplanets around M dwarfs: no evidence for a super-Earth in a 2-day orbit around GJ 1151 - Perger, Manuel; Ribas, I.; Anglada-Escudé, G.; Morales, J. C.; Amado, P. J.; Caballero, J. A.; Quirrenbach, Andreas; Reiners, A.; Béjar, V. J. S.; Dreizler, S.; Galadí-Enríquez, D.; Hatzes, A. P.; et al. (Astronomy and astrophysics, 2021)
Context. The interaction between Earth-like exoplanets and the magnetic field of low-mass host stars are considered to produce weak emission signals at radio frequencies. A study using LOFAR data announced the detection of radio emission from the mid M-type dwarf GJ 1151 that could potentially arise from a close-in terrestrial planet. Recently, the presence of a 2.5-M⊕ planet orbiting GJ 1151 with a 2-day period has been claimed using 69 radial velocities (RVs) from the HARPS-N and HPF instruments.Aims. We have obtained 70 new high-precision RV measurements in the framework of the CARMENES M-dwarf survey and use these data to confirm the presence of the claimed planet and to place limits on possible planetary companions in the GJ 1151 system.Methods. We analysed the periodicities present in the combined RV data sets from all three instruments and calculated the detection limits for potential planets in short-period orbits.Results. We cannot confirm the recently announced candidate planet and conclude that the 2-day signal in the HARPS-N and HPF data sets is most probably produced by a long-term RV variability, possibly arising from an outer planetary companion that has yet to be constrained. We calculate a 99.9% significance detection limit of 1.50 m s−1 in the RV semi-amplitude, which places upper limits of 0.7 M⊕ and 1.2 M⊕ on the minimum masses of potential exoplanets with orbital periods of 1 and 5 days, respectively.
Gesehen am 26.08.2021